2018
DOI: 10.1108/jhr-05-2018-020
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and perception of alcohol drinking among the Lahu people, Northern Thailand

Abstract: Purpose-The purpose of this paper is to understand the pattern and perception of alcohol drinking among the Lahu people in northern Thailand. Design/methodology/approach-A qualitative method was used to elicit information on the patterns and perceptions of alcohol drinking amongst the Lahu tribespeople. Question guidelines had been developed from literature reviews and approved by three experts in the field of public health and alcohol studies. A total of 21 participants of different ages and sexes from 3 sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Males preferred drinking local whisky over other beverages. Drinking alcohol was symbolic because it showed strong physical health and readiness to be a community leader [48]. In terms of the prevalence of alcohol use, we also found that the older age category had a higher prevalence than the younger age categories.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Males preferred drinking local whisky over other beverages. Drinking alcohol was symbolic because it showed strong physical health and readiness to be a community leader [48]. In terms of the prevalence of alcohol use, we also found that the older age category had a higher prevalence than the younger age categories.…”
Section: Discussionmentioning
confidence: 57%
“…However, in our study, we found that males tended to use alcohol more than females, which might be due to social norms. Most hill tribe people have fewer males than females [48]. Thus, increased acceptance of male but not female alcohol use was not our expectation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Faktor yang menyebabkan mereka mengkonsumsi alkohol karena pengaruh tingkat pendapatan, perilaku orang tua, pengaruh teman sebaya, rasa dan adaptasi budaya. ( Detpitukyon, S., Apidechkul, T., Sunsern, R., Anuwatnonthakate, A., Singhhorn, O., Putsa, B., & Thutsanti, 2018). Hal yang sama juga menyatakan tentang pengaruh budaya dalam kehidupan sosial.…”
Section: Pengaruh Budaya Terhadap Pola Konsumsiunclassified
“…They are classified into six main tribes: Akha, Lahu, Hmong, Yao, Lisu, and Karen [35]. Each tribe has their own culture, lifestyle, and level of acceptance for the use of alcohol and substances in their communities [36]. Most hill tribe people are of low socioeconomic status, and some of them do not possess Thai identification cards (ID cards), which are used for free access to all public services, including education and health care systems [37].…”
Section: Introductionmentioning
confidence: 99%